Modulation of Apoptosis Pathways by Oxidative Stress and Autophagy in β Cells - Wang, Maorong (Hindawi Publishing Corporation, 2012)
Human islets isolated for transplantation are exposed to multiple stresses including oxidative stress and hypoxia resulting in significant loss of functional β cell mass. In this study we examined the modulation of apoptosis pathway genes in islets exposed to hydrogen peroxide, peroxynitrite, hypoxia, and cytokines. We observed parallel induction of pro- and antiapoptotic pathways and identified several novel genes including BFAR, CARD8, BNIP3, and CIDE-A. As BNIP3 is an inducer of autophagy, we examined this pathway in MIN6 cells, a mouse beta cell line and in human islets. Culture of MIN6 cells under low serum conditions increased the levels of several proteins in autophagy pathway, including ATG4, Beclin 1, LAMP-2, and UVRAG. Amino acid deprivation led to induction of autophagy in human islets. Preconditioning of islets with inducers of autophagy protected them from hypoxia-induced apoptosis. However, induction of autophagy during hypoxia exacerbated apoptotic cell death. ER stress led to induction of autophagy and apoptosis in β cells. Overexpression of MnSOD, an enzyme that scavenges free radicals, resulted in protection of MIN6 cells from cytokine-induced apoptosis. Ceramide, a mediator of cytokine-induced injury, reduced the active phosphorylated form of Akt and downregulated the promoter activity of the antiapoptotic gene bcl-2. Furthermore, cytokine-stimulated JNK pathway downregulated the bcl-2 promoter activity which was reversed by preincubation with SP600125, a JNK inhibitor. Our findings suggest that β cell apoptosis by multiple stresses in islets isolated for transplantation is the result of orchestrated gene expression in apoptosis pathway.